Astragaloside IV ameliorates early diabetic nephropathy by inhibition of MEK1/2-ERK1/2-RSK2 signaling in streptozotocin-induced diabetic mice. Issue 7 (July 2018) - Song, Gaofeng; Han, Pengxun; Sun, Huili; Shao, Mumin; Yu, Xuewen; Wang, Wenjing; Wang, Dongtao; Yi, Wuyong; Ge, Na; Li, Shunmin; Yi, Tiegang
Objective: The aim of this study was to investigate the renoprotective effects and molecular mechanisms of astragaloside IV (AS-IV) in streptozotocin (STZ)-induced diabetic mice. Methods: Male C57BL/6 mice were injected intraperitoneally with STZ at 200 mg/kg body weight. AS-IV was administered for 8 consecutive weeks, beginning 1 week after STZ injection. Body weight, 24-hour urinary albumin excretion, and fasting blood glucose were measured. Kidney tissues were examined by histopathological analyses. Total levels and phosphorylation of mitogen-activated protein kinase 1/2 (MEK1/2), extracellular signal-regulated kinases 1 and 2 (ERK1/2), and ribosomal S6 kinase 2 (RSK2) were determined by Western blotting analysis. Results: AS-IV treatment significantly reduced albuminuria and serum creatinine levels, ameliorated mesangial matrix expansion and greater foot process width, and decreased the levels of urinary N-acetyl-beta-D-glucosaminidase, neutrophil gelatinase-associated lipocalin, and transforming growth factor-beta 1 in STZ-induced diabetic mice. AS-IV also inhibited renal cortical phosphorylation of MEK1/2, ERK1/2 and RSK2. Conclusion: Our results suggest that AS-IV attenuates renal injury in STZ-induced diabetic mice. This effect might be partially associated with inhibition of the activation of the MEK1/2-ERK1/2-RSK2 signaling pathway.